Computational Intelligence and Intelligent Systems 6th International Symposium, ISICA 2012, Wuhan, China, October 27-28, 2012. Proceedings - Li, Zhenhua; Li, Xiang; Liu, Yong.; Cai, Zhihua; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 6th International Symposium on Intelligence Computation and Applications, ISICA 2012, held in Wuhan, China, in October 2012. The 72 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on artificial life, adaptive behavior, agents, and ant colony optimization; combinatorial and numerical optimization; communications and computer networks; data mining; evolutionary multi-objective and dynamic optimization; intelligent computation, intelligent learning systems; neural networks; real-world applications.
Artificial life, adaptive behavior, agents, and ant colony optimization -- Combinatorial and numerical optimization -- Communications and computer networks -- Data mining -- Evolutionary multi-objective and dynamic optimization -- Intelligent computation, intelligent learning systems -- Neural networks -- Real-world applications.
Keywords: Computer science; Information theory; Computer software; Electronic data processing; Data mining; Computer Science; Theory of Computation; Computing Methodologies; Algorithm Analysis and Problem Complexity; Numeric Computing; Models and Principles; Data Mining and Knowledge Discovery